Intensive Care Unit Patients’ Perception of Sleep Quality and Factors of Sleep Disruption: Cross-sectional Study - Abbas Al Mutair; Abbas Shamsan; Adel AlFaqiri; Awad Al-Omari (Dr. Sulaiman Al Habib Medical Journal)
This study aimed to identify the etiologies of sleep deprivation among patients in the Intensive Care Unit (ICU). Sleep deprivation is a common problem that patients face while they are in the ICU. Poor sleep quality has several consequences such as weakening the immune system, irregular sleep cycle, and delirium. A cross-sectional study using self-administered questionnaire was performed in three medical—surgical ICU of tertiary teaching private hospitals. A modified version of sleep quality questionnaire developed by Freedman and colleagues was used to collect data from ICU patients. The questionnaire required patients to rate their overall sleep quality on a 10-point scale. A total of 30 patients participated in the study, and results showed that they perceived their overall sleep quality at home and the ICU at almost the same level. Findings also showed no differences in patients’ sleep quality during daytime and nighttime as well as during their 1st night, middle of their stay, and toward the end of ICU stay. Heart monitor alarms were perceived by the patients as the most disrupting noise in the ICU. Statistically significant differences were detected between gender and overall sleep quality (p = 0.001), daily activities (p = 0.003), and noises (p = 0.0005). Patients who had been in the ICU for 4–7 days were found to have a statistically significant poorer sleep quality compared with other patients. Multifactorial causes, including environmental and nonenvironmental factors, can result in sleep disruption among ICU patients. Interventions and strategies should be developed to minimize sleep disruption and improve the quality of care provided to ICU patients.